2013
DOI: 10.3844/ajidsp.2013.136.141
|View full text |Cite
|
Sign up to set email alerts
|

The €œNEW SETTLERS”: RESULTS OF a BACTERIOLOGICAL SURVEY DURING THE FIRST 6-Months OPERATION PERIOD OF AN INTERNAL MEDICINE WARD IN a TERTIARY HOSPITAL

Abstract: During the first six months of operating a new Internal-medicine ward in a tertiary hospital, a prospective survey, tracking both patient and environment bacteriological samples taken, was conducted. The motive behind the study was to establish the pattern in which environmental colonization is transmitted to the hospitalized patients and vice versa, thus defining the nosocomial pathogens that are typical to the ward. That information can be used to guide empirical antibiotic treatment. Patient sampling was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Aging and diabetes mellitus, which might exacerbate infectious diseases, were also risk factors for prolongation of hospitalization. Regulation and control of infectious diseases during hospitalization has been enforced by the infectious diseases control division in the hospital, ( 13 , 15 , 16 ) and the present study clearly demonstrated the importance of infectious disease control during hospitalization.…”
Section: Discussionsupporting
confidence: 64%
“…Aging and diabetes mellitus, which might exacerbate infectious diseases, were also risk factors for prolongation of hospitalization. Regulation and control of infectious diseases during hospitalization has been enforced by the infectious diseases control division in the hospital, ( 13 , 15 , 16 ) and the present study clearly demonstrated the importance of infectious disease control during hospitalization.…”
Section: Discussionsupporting
confidence: 64%
“…In statistical aspect, there are many association measures available to measure the dependency between the variables. Segal et al (2013) applied the association measures on their work. But all the association measures are not going to produce interestingness rules due to the over whelming of data and by existence of the redundant rules on mined patterns.…”
Section: Introductionmentioning
confidence: 99%